ENHANCING COMMUNITY ENVIRONMENTAL AWARENESS THROUGH INDOOR AIR QUALITY WORKSHOP - Kencanasari, R.A Vesitara; Surahman, Usep; Permana, Asep Yudi; Nugraha, Hari Din (Universitas Pendidikan Indonesia, 2020)
Abstract - This research is motivated by the poor air quality in the room at home that can cause Sick Building Syndrome (SBS). The purpose of this research is to increase public awareness of the environment through indoor air quality workshops, with a Pre-Experimental method and One Group Pre-Test Post-Test research design. The sample in this study was Pasteur RW6, Sukajadi District at Bandung City, which was selected based on criteria including non slum areas, as well as high community participation. The results showed that the level of public awareness, knowledge, attitudes, and actions on air quality in the room before the Workshop was in the medium category. Then it increased after the Workshop, which was on a relatively moderate increase in knowledge. This can be seen from the majority of people who already know the importance of indoor air quality, but the knowledge of specific components that affect indoor air quality is still not understood. Whereas attitudes and actions experienced a relatively small increase due to the knowledge gained in the Workshop not being implemented in the form of real attitudes and actions in daily life because people's habits are difficult to change.Â Keywords â€“ Environmental Awareness, Indoor Air Quality, Workshop, Community AwarenessÂ